Differences in Reaction to Immediate Feedback and Opportunity to Revise Answers for Multiple-Choice and Open-Ended Questions. (October 2016) - Attali, Yigal; Laitusis, Cara; Stone, Elizabeth
There are many reasons to believe that open-ended (OE) and multiple-choice (MC) items elicit different cognitive demands of students. However, empirical evidence that supports this view is lacking. In this study, we investigated the reactions of test takers to an interactive assessment with immediate feedback and answer-revision opportunities for the two types of items. Eighth-grade students solved mathematics problems, both MC and OE, with standard instructions and feedback-and-revision opportunities. An analysis of scores based on revised answers in feedback mode revealed gains in measurement precision for OE items but not for MC items. These results are explained through the concept of effortful engagement—the OE format encourages more mindful engagement with the items in interactive mode. This interpretation is supported by analyses of response times and test takers' reports.